The climate adaptation trilemma - Ilan Noy; Tomáš Uher (EconPol Forum, 2025)
Climate adaptation requires weighing trade-offs associated with every adaptation policy choice.Trade-offs can be described as a Trilemma of choosing between two out of three goals: reducing inequities and hardship, incentivizing risk reduction, and fiscal sustainability. Three main approaches dominate adaptation and align with these goals: government investment, private adaptation, and risk finance and insurance. Economic assessments of adaptation policies should increasingly strive to include ancillary and indirect effects and quantify the Trilemma trade-offs. Combinations of adaptation policies should be designed to minimize trade-offs and maximize synergies.
Keywords: 330